Intraoperative JJ-stent placement during laparoscopic procedure - A. D. Kochkin (Вестник урологии)
Various options of JJ placement during different laparoscopic upper urinary tract procedures are described herein “Tips & Tricks” manner. Author’s “Lifehacks” to make this manipulation easier is also presented.